REPRESENTAÇÃO DO RELEVO SUBMERSO E IDENTIFICAÇÃO DE ELEMENTOS SOB A PONTE JK POR AQUISIÇÃO E PROCESSAMENTO DE DADOS EM LEVANTAMENTO BATIMÉTRICO MONOFEIXE - Freitas, Érik Luiz; Brito, Marcus Alexandre Noronha de; Bezerra, Luciano Mendes; Silva, Willian Taylor Matias (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Since the mid-nineteenth century, man has been trying to improve their knowledge of the seabed. At present, this study is necessary in hydraulic works, both in determining how to monitor the areas to be dredged, in the lease of gas pipelines and transoceanic cables, oil exploration and other mineral resources in research, monitoring processes erosion or siltation, navigation, monitoring bridges and environmental preservation. For investigation of submerged areas, be they shallow or deep, the bathymetric acoustic method generates a number or numerical database mapped able to define the surface morphology and identify structural elements of a bridge, for example, as adopted to the bridge JK in Brasilia. Still, the treatment of numerical arrays acquired allow mathematical adjustments in order to correct data by field collection enforcement issues can distort or generate incomplete information. Thus, the method helps many constructive processes of engineering with precision required in relation to interference or submerged elements necessary IDs.